2016
DOI: 10.1002/jcb.25682
|View full text |Cite
|
Sign up to set email alerts
|

High Mobility Group Box 1 Mediates Interferon-γ-Induced Phenotypic Modulation of Vascular Smooth Muscle Cells

Abstract: The phenotypic modulation of VSMCs is a key cellular event driving neointimal formation and vascular remodeling. As a multifaceted cytokine of cell-mediated immunity, IFN-γ has been shown to play a critical role in the pathogenesis of vascular proliferative diseases. Although the important function of IFN-γ on regulating VSMC activation is well established, the molecular mechanisms by which elicits VSMC responses are poorly defined. Recent studies have identified HMGB1 as a principal effector to mediate IFN-γ-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 52 publications
0
17
0
Order By: Relevance
“…BrdU incorporation assay was performed to assess cell proliferation as previously described [ 28 ]. Suspended cells were seeded into 96-well plates at a density of 5 × 10 3 cells per well, allowed to attach and grow overnight.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…BrdU incorporation assay was performed to assess cell proliferation as previously described [ 28 ]. Suspended cells were seeded into 96-well plates at a density of 5 × 10 3 cells per well, allowed to attach and grow overnight.…”
Section: Methodsmentioning
confidence: 99%
“…VSMC migration was evaluated by wound-healing and Transwell migration assays as previously desired [ 28 ]. About ~90% confluence, cells were starved for 48 h prior to scratch wounding.…”
Section: Methodsmentioning
confidence: 99%
“…The phenotypic modulation of VSMCs is a key cellular event that drives neointima formation and vascular remodeling. Reportedly, the phenotypic modulation of VSMCs induced by interferon-γ is mediated by high mobility group box-1 (HMGB1), a non-histone chromosomal protein (Wang et al, 2017 ). HMGB1 is released by monocytes/macrophages in response to inflammatory stimuli and then binds to DNA in a sequence-independent manner and modifies DNA structure, and thereby facilitates gene transcription (Kalinina et al, 2004 ; Stott et al, 2006 ; Yang et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…In blood vessels, high levels of extracellular HMGB1 have been detected in human atherosclerotic plaque, and reportedly are implicated in vascular inflammation by potentiating inflammatory responses (Kalinina et al, 2004 ; Cai et al, 2015 ). It has also been shown that HMGB1 modulates the phenotype of VSMCs toward the activated synthetic phenotype and stimulates MCP-1/CCL2 gene expression through toll-like receptor 4 (TLR4) (Cai et al, 2015 ; Wang et al, 2017 ). However, the nature of the links between VSMCs, HMGB1, and vascular inflammation have not been clarified.…”
Section: Introductionmentioning
confidence: 99%
“…Coronary arterial myocytes are the primary cell type in blood vessel walls and play essential roles in pathogenesis of vascular diseases. By transforming from the contractile to the synthetic phenotype, the CAMs exhibit distinct proliferative and migratory abilities and produce pro-inflammatory cytokines (Wang K. et al, 2017;Zhang et al, 2018). HMGB1 was demonstrated to stimulate cell proliferation and migration in a variety of mammalian cells including fibroblasts (Chitanuwat et al, 2013), airway SMCs (Hou et al, 2019), osteosarcoma cells (Guo et al, 2014), and cancer cells (He et al, 2018).…”
Section: Discussionmentioning
confidence: 99%